Policy Directions for Early Childhood Education Teacher Development in Indonesia in the Merdeka Belajar Era: A Systematic Literature Review - Zaida, Nur Aini; Hartati, Sofia; Dhieni, Nurbiana; Akhlak, Faza Karimatul; Hidjanah (JOYCED: Journal of Early Childhood Education, 2026)
Purpose – Existing studies on Early Childhood Education (ECE) teacher development in Indonesia during the Merdeka Belajar era remain fragmented. This study aims to synthesize evidence on policy directions, implementation challenges, and recommendations for ECE teacher development. Design/methods/approach – A Systematic Literature Review guided by the PRISMA 2020 framework was conducted. Data were retrieved from Google Scholar using Publish or Perish with six keyword combinations related to ECE policy, teacher development, Merdeka Belajar, and the Merdeka Curriculum. From 120 initial records, 30 studies were selected and analyzed through thematic synthesis involving coding and theme development. Findings – Five themes emerged: policy and regulatory development, teacher professional development, Merdeka Curriculum implementation, digital literacy and technology integration, and implementation challenges with future policy recommendations. The findings indicate a shift toward curriculum flexibility, child-centered learning, authentic assessment, teacher autonomy, and contextual learning practices, providing practical directions for strengthening ECE teacher development policies. The findings highlight ECE teacher development as a systemic process shaped by policy, institutional support, and professional learning. Research implications/limitations – Strengthening ECE teacher development requires sustained mentoring, professional learning communities, digital inclusion, welfare support, and impact-based evaluation. The review is limited to studies retrieved from Google Scholar using selected keywords. Originality/value – This study provides a comprehensive synthesis of policy directions, challenges, practical insight and recommendations for strengthening ECE teacher development in Indonesia. Article classification – Systematic Literature Review.